2020
DOI: 10.21203/rs.3.rs-16707/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between nonalcoholic fatty liver disease and extrahepatic cancers: a systematic review and meta-analysis

Abstract: Background: NAFLD is tightly associated with various diseases such as diabetes, cardiovascular disease, kidney disease, and cancer. Previous studies had investigated the association between NAFLD and various extrahepatic cancers, but the available data to date is not conclusive. The aim of this study was to investigate the association between NAFLD and various extrahepatic cancers comprehensively. Methods: Searches were conducted of various electronic databases (PubMed, EMBASE, Medline, and the Cochrane Librar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…In a meta‐analysis, Liu et al investigated the association between NAFLD and the risk of cholangiocarcinoma, colon, breast, gastric, pancreatic, prostate and oesophageal cancer 32 . In logistic regression, NAFLD was associated with colorectal (odds ratio [OR] 1.72 [ p < .01]), gastric (OR 1.74 [ p = .01]) and prostate cancer (OR 1.36 [ p < .01]) 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta‐analysis, Liu et al investigated the association between NAFLD and the risk of cholangiocarcinoma, colon, breast, gastric, pancreatic, prostate and oesophageal cancer 32 . In logistic regression, NAFLD was associated with colorectal (odds ratio [OR] 1.72 [ p < .01]), gastric (OR 1.74 [ p = .01]) and prostate cancer (OR 1.36 [ p < .01]) 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis, Liu et al investigated the association between NAFLD and the risk of cholangiocarcinoma, colon, breast, gastric, pancreatic, prostate and oesophageal cancer 32 . In logistic regression, NAFLD was associated with colorectal (odds ratio [OR] 1.72 [ p < .01]), gastric (OR 1.74 [ p = .01]) and prostate cancer (OR 1.36 [ p < .01]) 32 . The heterogeneity between the studies investigating colorectal, gastric and prostate cancers was significant ( I 2 83.5% for colorectal, 73.6% for gastric and 81.9% for prostate cancer).…”
Section: Discussionmentioning
confidence: 99%
“…From their analysis, they determined that the odds of developing CRC in patients with NAFLD were almost doubled, while the odds for developing intrahepatic cholangiocarcinoma and extrahepatic cholangiocarcinoma in patients with NAFLD were increased 2.5 times compared to those without NAFLD. The odds of developing breast cancer gastric cancer, pancreatic cancer, prostate cancer and oesophageal cancer were also found to be significantly increased 149 . However, another study from Sweden found that the presence of NAFLD was only modestly associated with increased rates of pancreatic cancer, kidney/bladder cancer and melanoma but no other cancers 150 .…”
Section: Extra Hepatic Cancer and Nafld Mortalitymentioning
confidence: 95%
“…NAFLD not only contributes to the development of liver cirrhosis and cardiovascular complications but also acts as an etiological factor for cancer initiation and progression. A systemic review and meta-analysis concluded that NAFLD may trigger hepatocellular, colorectal, breast, pancreatic, prostate, and esophageal cancer [ 23 , 24 ]. Though the exact mechanism underlying NAFLD-induced cancer is not well-established, the possible contributing factors may include unregulated efflux of adipokines, increased levels of IGF-1, insulin, and cytokines (TNF- α , IL-6), accelerated hepatocyte proliferation, lipid peroxidation, oxidative stress, DNA damage, and lipotoxicity [ 25 29 ].…”
Section: Pathophysiology Of Hepatic Disorders and Dmmentioning
confidence: 99%